Правильное питание – основа здоровья и долголетия - Щербакова, Галина Дмитриевна (My University, 2016)
Питание — это совокупность процессов и функций, которые определяют рост, развитие, существование и воспроизводство организма. Оно подразумевает постоянное обновление тканей, снабжение их питательными веществами, а не только накопление жира или «стимуляция» (возбуждение) жизненных сил. The goal of research is to prove the necessity of proper nutrition, consider useful functions of water, analyze the positive and negative effects on the food organism. It was conducted the analysis of educational literature, observation, comparison of the results. It are presented options for nutrition, proved the importance of water metabolism in the body. The goal of research is to prove the necessity of proper nutrition, consider useful functions of water, analyze the positive and negative effects on the food organism. It was conducted the analysis of educational literature, observation, comparison of the results. It are presented options for nutrition, proved the importance of water metabolism in the body.
Keywords: здоровье; питание; health; food; кафедра фізичного виховання